Social Awareness Education for Children with Autism Spectrum Disorder Aged 5-6 Years Through Experiential Activities at Inclusive Kindergarten - Nguyen, Quynh Nhu Thi; Do, Thao Thi; Nguyen, Khanh Cong; Hoang, Nho Thi; Thi, Anh Thu Nguyen; Nguyen, Vu Phi (Journal of Ecohumanism, 2025)
This study examines the effectiveness of experiential activities in enhancing social awareness among children aged 5–6 years with Autism Spectrum Disorder (ASD) in inclusive kindergarten settings. Grounded in social-cognitive theory, experiential learning theory, and Vygotsky’s socio-cultural theory, the research explores how hands-on, interactive activities contribute to the development of emotional recognition, social engagement, and behavioral regulation. A 15-week intervention was conducted with three children diagnosed with mild ASD, integrating structured social games, storytelling, and role-playing activities. Results indicate significant improvements in emotional recognition, appropriate emotional expression, and social interaction in two of the three children, underscoring the potential of experiential activities as an effective approach to fostering social awareness. The findings highlight the importance of a supportive and interactive learning environment in promoting social inclusion and adaptive behaviors in young children with ASD.